Determinants of Operational Performance among Brimob Personnel: The Roles of Tactical Training, Work Motivation, and Competence - Renil Septiano; Angga Putra (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the effects of tactical training, work motivation, and competence on the operational performance of Brimob Company 3 members in Sungai Penuh City. The study was designed as causal quantitative research. The population consisted of all 60 personnel in the unit, and because the population was fully accessible, the study used saturated sampling. Data were collected through a Likert scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling using SmartPLS. The measurement model met the required validity and reliability criteria after several indicators with inadequate loadings were removed. The structural model showed that tactical training had a positive and significant effect on operational performance with a path coefficient of 0.398 and a probability value of 0.000. Work motivation also had a positive and significant effect with a coefficient of 0.277 and a probability value of 0.017. Competence had the strongest positive and significant effect with a coefficient of 0.429 and a probability value of 0.000. The model explained 47.6 percent of the variance in operational performance, indicating moderate explanatory power. These findings confirm that performance improvement in tactical police units requires stronger training quality, sustained work motivation, and systematic competence development.